An analysis of counterproductive workplace behaviours - Chong, Hui Yu (2019)
Counterproductive Workplace Behaviour (CWB) easily goes unnoticeable in many organizations, this penalized organizations a huge cost. Therefore, in recent years many researches had been done in Western country to explore the causes of CWB from different constructs. Many factors could influence CWB, for example personality traits, quality of leadership, job environment, and internal control. CWB will reduce productivity, motivation, and cause many problems to organization. Therefore, to contribute to the gap of research in Asian Country about CWB, this study tends to examine the causes of CWB in Malaysia. Four independent variables which were Narcissism, Machiavellianism, Psychopathy, and Job Constraints had been adopted in this research to identify the causes of CWB. A total of 225 respondents in Malaysia were participated and responded in this survey. Based on the findings and analysis, this study revealed that there are two independent variables that have positive significant relationship in affecting the CWB which are Psychopathy and Job Constraints. Hopefully, these findings can be used by manager and organization in Malaysia to develop a good recruitment procedure to avoid recruiting candidates with high CWB characteristics. Lastly, based on the findings, the researcher also suggested a few recommendations for further study and improvement.